Fenomena Cyberporn dalam Optik Hukum Pidana - M. Abdul Kholiq (Fakultas Hukum Universitas Islam Indonesia, 2007)
Principally, the phenomenon of cyber porn has been provided in the existing criminal laws, both in the Code of Criminal Law (KUHP) or in other regulations. However, it should be considered that these existing laws need for reformation and enhancement in order to be more effective in their enforcement. More stronger punishment and clearer jurisdiction in handling the cases are among the aspects which shall be covered by the amendment.